Improved Reactivity in the Ring-Opening Polymerization of ε-Caprolactone with a Trinuclear Titanium(IV) Oxochloroneopentoxide as Initiator - Giese,Siddhartha O. K. (2017)
The complex [Ti3(O)(Cl)(ONep)9] and two iron(II)-containing products, [Fe4Cl8(thf)6] and [Fe2Cl3(thf)6][FeCl4], were synthesized by a redox reaction involving [Ti3(OiPr)11][FeCl4] and neopentanol; the structures of compounds [Ti3(O)(Cl)(ONep)9] and [Fe2Cl3(thf)6][FeCl4] have been confirmed by X-ray diffraction methods. Variable-temperature 1H NMR analysis of [Ti3(O)(Cl)(ONep)9] revealed signals for three non-equivalent neopentoxides in the 1:1:1 integration ratio, indicating the maintenance of the trinuclear structure in solution. Alkoxide [Ti3(O)(Cl)(ONep)9] was employed as initiator in both bulk and solution polymerization of ε-caprolactone (ε-CL) at various temperatures, monomer/initiator molar ratios and reaction times. [Ti3(O)(Cl)(ONep)9] produced poly(ε-caprolactone) in high yields, with molecular weights ranging from 7100 to 9800 g mol-1 and PDI (polydispersity index) values between 1.3 to 1.5. The reactivity of [Ti3(O)(Cl)(ONep)9] in the ring-opening polymerization (ROP) of ε-CL was compared to those of [Ti3(OiPr)11][FeCl4] and [Ti(OiPr)4]. The better polymerization reactivity shown by [Ti3(O)(Cl)(ONep)9] seems to be associated with structural features, as well as with the stronger Lewis basicity of -ONep over -OiPr ligands and the maintenance of the trimetallic structure in the reaction media.